Managing Innovation and Operations in the 21st Century - Garza-Reyes, Jose Arturo; Kumar, Vikas; Martinez-Covarrubias, Juan Luis.; Lim, Ming K. (Boca Raton, FL : CRC Press, 2017)
"This book is for directors, consultants, practitioners, and professionals aspiring to effectively manage operations, but is targeted at applying innovation to the management of operations, including supply chains. It is appropriate for those establishing a career in innovation and operations management. This book will: Equip readers with understanding of the nature of innovation, operations management concepts, business models, methods and tools; Explore best practices and most commonly used operations and innovation business models, methods, and tools used by successful organisations; Consider particular operational issues directly impact the competitiveness of organisations"--Provided by publisher.
Part Section I: Undiferstanding the General Context -- chapter 1 Undiferstanding the General Context and Link between Innovation and Operations Management -- chapter 2 Economics of Innovation and Operations -- part Section II: Undiferstanding the External Context -- chapter 3 Location, Location, Location: External Determinants of Innovation Performance -- chapter 4 Innovation in Global Supply Chain Management -- part Section III: Undiferstanding the Internal context -- chapter 5 The Role of Operations Managers in Building a Culture of Innovation and Continuous Improvement -- chapter 6 Getting the Right Organizational Structure and Working Environment to Balance Innovation and Efficiency -- chapter 7 New Product/Service Design and Innovation in the Context of Operations -- chapter 8 What Operations Managers Need to Know to Design Innovative Processes -- chapter 9 Innovation and Sustainability -- chapter 10 Going Beyond Managing{u2014}Improving Existing Services and Processes.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Purchasing & Buying; Industrial management; Management science; Organizational effectiveness; Technological innovations -- Management